1999
DOI: 10.1021/jf981044i
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Tannin with Human Salivary Histatins

Abstract: The ability of all major human salivary histatins to precipitate condensed tannin was demonstrated, and it was found that histatins 3 and 5 share the same condensed tannin-binding region but less tannin bound to histatin 1. The condensed tannin-binding region of histatin 5 includes both the N- and the C-terminal parts, although more tannin binding occurs in the C-terminal region. Epigallocatechin gallate (EGCG) showed similar binding characteristics as condensed tannin, but much less EGCG was precipitated. Pen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(64 citation statements)
references
References 27 publications
4
59
0
1
Order By: Relevance
“…At a low concentration of condensed tannin or tannic acid, histatins were more readily precipitated from saliva than PRPs, and more condensed tannin and tannic acid were precipitated by histatin than gelatin at neutral pH, demonstrating the effectiveness of histatin in precipitating tannin. Further studies (Naurato et al ., 1999) indicated that Histatins 3 and 5 apparently share the same condensed tannin-binding region, which is located throughout the shared histatin 5 sequence, and they bound more condensed tannin than histatin 1. Epigallocatechin gallate (EGCG) showed binding characteristics similar to those of condensed tannin, while pentagalloyl glucose (PGG) bound equally well to histatins 1, 3, and 5.…”
Section: (Viii) Interaction Of Salivary Proteins and Tanninmentioning
confidence: 93%
“…At a low concentration of condensed tannin or tannic acid, histatins were more readily precipitated from saliva than PRPs, and more condensed tannin and tannic acid were precipitated by histatin than gelatin at neutral pH, demonstrating the effectiveness of histatin in precipitating tannin. Further studies (Naurato et al ., 1999) indicated that Histatins 3 and 5 apparently share the same condensed tannin-binding region, which is located throughout the shared histatin 5 sequence, and they bound more condensed tannin than histatin 1. Epigallocatechin gallate (EGCG) showed binding characteristics similar to those of condensed tannin, while pentagalloyl glucose (PGG) bound equally well to histatins 1, 3, and 5.…”
Section: (Viii) Interaction Of Salivary Proteins and Tanninmentioning
confidence: 93%
“…Similarly, the profisetinidin CTs from quebracho interacted with salivary histatins by a different mode than PGG. 246 Although it has been known for some time that the binding strengths in different tannin-protein complexes can vary over orders of magnitude, 87 surprisingly few studies have related the protein-binding abilities of tannins to in vivo protein digestibilities. Robbins et al 143 concluded that the reduction in protein digestibility in wild ruminants was proportional to the BSA protein-precipitating capacity of plant tannins.…”
Section: Protein Precipitation Assaysmentioning
confidence: 99%
“…Several studies report the role of salivary PRPs and HRPs in binding phenolic compounds [2,3,5,7,9,29], therefore the focus here is directed toward the binding to a-amylase. Saliva amylase contains 22 proline and 16 tryptophan amino acid residues in its sequence (NCBI Protein data bank).…”
Section: Tryptophan Quenching Experimentsmentioning
confidence: 99%